THE IMPACT OF THE CURRICULUM OF PHYSICAL EDUCATION ON THE PHYSICAL, KINETIC, PHYSIOLOGICAL, AND SKILLS VARIABLES AMONG THE NORTHERN BADIA EASTERN STUDENTS - Ismael Al-Oun; Rania Shaddad Qutaishat (European Scientific Journal, ESJ, 2015)
The aim of this study is to assess the impact of the curriculum of physical education on the physical, kinetic, physiological, and skill variables of the Northern Badia Eastern students. A study of all the teachers of physical education at the basic stage of the Directorate of Education of the brigade Northern Badia East schools was carried out. Due to the small size of the study population, a total of 181 teachers who teaches physical education were used for the purpose of this study. The researcher uses a questionnaire for the purpose of data collection. The questionnaire consists of two parts. The first include personal information about the members of the study, such as gender, educational qualification, and experience. The second consists of 10 phrases. After data collection and discharged, it was processed using suitable descriptive statistical and analytical methods. The study showed the results to assess the impact of physical education curriculum on the physical and motor skills. In addition, the results show the physiological variables at the north-eastern desert students (medium), where the mean was the responses of the study sample (3.53: 5.00). The existence of differences is statistically attributed to the variable gender in favor of females. Also, the differences are attributable to the qualification variable in favor of less than BA category. Finally, the researcher recommended a number of recommendations due to the lack of differences attributable to variable experience, and in light of the results of this study.